2018
DOI: 10.1038/s41419-018-0538-5
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps promote macrophage pyroptosis in sepsis

Abstract: In response to infection, polymorphonuclear neutrophils (PMN) are recruited in the infectious sites, and employ three major strategies to fight against the microbes including phagocytosis, degranulation, and neutrophil extracellular traps (NETs). NETs are a meshwork of chromatin fibers mixed with granule-derived antimicrobial peptides and enzymes, which trap and kill the bacteria extracellularly. In this study, by using a mouse sepsis model, we identified a novel mechanism by which NETs induce macrophage (Mϕ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 37 publications
(43 reference statements)
3
89
0
1
Order By: Relevance
“…This latter status was thought to occur through a variety of detrimental factors that consequently lead to immune cell shortage or dysfunction. In recent years, more attention has been attracted to the role of pyroptosis of immune cells in immune disorder of sepsis [6,17,18]. In the current study, we found that the percentages of pyroptotic PBMCs in nonsurvivors were significantly higher than those of the survivors in trauma-induced sepsis.…”
Section: Discussionsupporting
confidence: 54%
“…This latter status was thought to occur through a variety of detrimental factors that consequently lead to immune cell shortage or dysfunction. In recent years, more attention has been attracted to the role of pyroptosis of immune cells in immune disorder of sepsis [6,17,18]. In the current study, we found that the percentages of pyroptotic PBMCs in nonsurvivors were significantly higher than those of the survivors in trauma-induced sepsis.…”
Section: Discussionsupporting
confidence: 54%
“…Extracellular histones, which have been reported to activate NLRP3 inflammasome (Allam et al, 2013), are associated with a variety of inflammation and diseases. And it has been reported that neutrophil extracellular traps (NETs), in which histone H3 is a key component, can promote macrophage pyroptosis in sepsis (Chen et al, 2018). Once released from the nucleosome, extracellular histones exert their damaging effects in three ways:…”
Section: Discussionmentioning
confidence: 99%
“…The role of cGAS‐STING signaling in the exacerbation of other inflammatory (severe eosinophilic asthma, eosinophilic chronic rhinosinusitis, RA, and psoriasis) diseases associated with the frequent release of extracellular traps needs attention . The release of NETs by neutrophils causes pyroptosis of Mϕs further augmenting the inflammatory process . It will be interesting to observe the impact of Mϕ pyroptosis on the cGAS‐STING signaling pathway in above mentioned autoimmune diseases where NETosis plays a significant role in the immunopathogenesis.…”
Section: Cgas‐sting Signaling In Autoinflammation and Autoimmunitymentioning
confidence: 99%